3D Nanoprinting of Perovskites. Issue 44 (23rd September 2019) - Chen, Mojun; Yang, Jihyuk; Wang, Zhenyu; Xu, Zhaoyi; Lee, Heekwon; Lee, Hyeonseok; Zhou, Zhiwen; Feng, Shien‐Ping; Lee, Sanghyeon; Pyo, Jaeyeon; Seol, Seung Kwon; Ki, Dong‐Keun; et al.
Abstract: As competing with the established silicon technology, organic–inorganic metal halide perovskites are continually gaining ground in optoelectronics due to their excellent material properties and low‐cost production. The ability to have control over their shape, as well as composition and crystallinity, is indispensable for practical materialization. Many sophisticated nanofabrication methods have been devised to shape perovskites; however, they are still limited to in‐plane, low‐aspect‐ratio, and simple forms. This is in stark contrast with the demands of modern optoelectronics with freeform circuitry and high integration density. Here, a nanoprecision 3D printing is developed for organic–inorganic metal halide perovskites. The method is based on guiding evaporation‐induced perovskite crystallization in mid‐air using a femtoliter ink meniscus formed on a nanopipette, resulting in freestanding 3D perovskite nanostructures with a preferred crystal orientation. Stretching the ink meniscus with a pulling process enables on‐demand control of the nanostructure's diameter and hollowness, leading to an unprecedented tubular‐solid transition. With varying the pulling direction, a layer‐by‐layer stacking of perovskite nanostructures is successfully demonstrated with programmed shapes and positions, a primary step for additive manufacturing. It is expected that the method has the potential to create freeform perovskite nanostructures for customized optoelectronics. Abstract : 3D nanoprinting of organic–inorganic metal halide perovskites is realized with guiding crystallization using a femtoliter ink meniscus in mid‐air.